2011
DOI: 10.1017/s0954394511000135
|View full text |Cite
|
Sign up to set email alerts
|

Variability in American English s-retraction suggests a solution to the actuation problem

Abstract: Although formulated by Weinreich, Labov, and Herzog in 1968, the actuation problem has remained an unsolved problem in understanding sound change: if sound change is conceived as the accumulation of coarticulation, and coarticulation is widespread, how can some speech communities resist phonetic pressure to change? We present data from American English s-retraction that suggest a partial solution. S-retraction is the phenomenon in which /s/ is realized as an [ʃ]-like sound, especially when it occurs in an /stɹ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
151
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(166 citation statements)
references
References 29 publications
10
151
0
Order By: Relevance
“…It is well established in sociolinguistic studies that the phonological system of any language is constantly undergoing some form of change (Labov, 1994, and references therein). This usually protracted phenomenon is realized in the form of variable patterns of perception and production across individuals in a community that is assumed to be otherwise linguistically homogeneous (Baker, Archangeli, & Mielke, 2011;Beddor, 2009;Koenig, Lucero, & Perlman, 2008). Therefore, the present investigation aims to understand individual variations in speech processing, particularly the mismatch between perception and production emerging from an ongoing sound change with respect to internal factors of cognitive abilities.…”
mentioning
confidence: 99%
“…It is well established in sociolinguistic studies that the phonological system of any language is constantly undergoing some form of change (Labov, 1994, and references therein). This usually protracted phenomenon is realized in the form of variable patterns of perception and production across individuals in a community that is assumed to be otherwise linguistically homogeneous (Baker, Archangeli, & Mielke, 2011;Beddor, 2009;Koenig, Lucero, & Perlman, 2008). Therefore, the present investigation aims to understand individual variations in speech processing, particularly the mismatch between perception and production emerging from an ongoing sound change with respect to internal factors of cognitive abilities.…”
mentioning
confidence: 99%
“…Previous studies have identified several aspects of systematic heterogeneity among individuals, e.g., speech perception (Beddor, 2009), speech production (Baker, Archangeli, & Mielke, 2011), the mapping between perception and production (Stevens & Reubold, 2014) and cognitive processing style (Yu, 2010), which have elucidated how sound change occurs and progresses within a particular community. For instance, Beddor (2009) has proposed that sound change can arise from idiosyncratic perception grammar; specifically, individual variation in perceptual analysis of coarticulatory variation would result in variation in phonological representations.…”
Section: Discussionmentioning
confidence: 99%
“…At least two pre-conditions would have to be met for post-aspiration to be imitated and to be spread within the speech community or, in other words, for the sound change to be actuated: First, the longer VOT needs acoustically to be sufficiently distinct in order to be perceived as a different production target (see Baker et al, 2011). Second, post-aspiration should not be perceived as a deviant /sC/-token because then, post-aspiration would be filtered out and would not be imitated by the listener when he becomes speaker (Garrett & Johnson, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Why should a listener take up a pronunciation form that deviates from what he usually hears? Baker et al (2011) suggest that sound change arises from the individual differences in coarticulation among speakers, arguing that "if every speaker produces essentially the same amount of coarticulation, then there is nothing to imitate in the first place" (Baker et al, 2011, p. 350). Only if the phonetic effect of coarticulation is large enough and perceptible can the listener interpret it as a different production target, and only then can it be imitated.…”
Section: Sound Change Actuationmentioning
confidence: 99%
See 1 more Smart Citation